Semantic priming in major depressive state - Georgieff, Nicolas; Ford Dominey, Peter; Michel, François; Marie-cardine, Michel; Dalery, Jean (Psychiatry research, 1998)
We studied semantic priming in 20 major depressive subjects. The methodology used was a visual lexical decision task. Semantic priming is the facilitation of target word recognition (shortening of response time) by the prior presentation of a semantically related context (a prime word). It relies on semantic processing of words and context, facilitating early cognitive stages of response. Varying the temporal interval between prime and target words onset allows us to distinguish between two priming mechanisms, relying on more automatic (test 1) or more controlled (i.e. attention dependent) (test 2) information processing. We observe a significant retardation for words and pseudo-words in depressives (in relation to controls) in both tests. In spite of a general retardation and increase of response times in depressives, semantic priming is evident in both groups and both tests, and does not differ significantly between depressive and control groups in either automatic or controlled conditions. Theses results confirm that semantic processing is not impaired in depression, and are discussed with regard to the hypothesis of an effortful processing impairment in depression, and to depressive retardation.